Glycan-specific precipitation of glycopeptides in high organic content sample solvents used in HILIC - Kozlik, Petr (J Chromatogr B Analyt Technol Biomed Life Sci, 2020)
The composition of a sample solvent has a crucial impact on separations in hydrophilic interaction liquid chromatography (HILIC). In this short communication, we studied the effect of an organic modifier in the sample solvent on the solubility of different tryptic glycopeptides of hemopexin and haptoglobin proteins. The results showed that the solubility of glycopeptides in solvents with a high acetonitrile content depends on the type of attached N-glycan. We observed lower solubility in larger glycans attached to the same peptide backbone, and we demonstrated that glycopeptides containing sialic acids precipitate more readily than those without sialic acid. Therefore, the sample solvent composition in HILIC must be carefully optimized for accurate quantitative data collection and for adequate separation.